P4.60 How does sexual health clinic attendance relate to risk behaviour? findings from britain's third national survey of sexual attitudes and lifestyles (NATSAL-3). (8th July 2017) - Ch, Mercer; Geary, Rebecca; Tanton, Clare; Clifton, Soazig; Mapp, Fiona; Cassell, Jackie; Sonnenberg, Pam
Abstract : Introduction: In Britain, sexual health clinics (SHC) attendance has increased in recent decades. SHC remain the commonest place of STI diagnosis but many with STI risk behaviours do not attend. We explored attendance patterns and service preferences in those reporting 'unsafe sex' (condomless first sex with new partner and/or ≥2 partners with no condom use, past year). Methods: Complex survey analyses of Natsal-3, a probability survey of 15 162 people aged 16–74 years (6293 men), undertaken 2010–2012 using computer-assisted personal- and self-interviewing (CAPI/CASI). Results: Overall, recent SHC attendance (past year) was highest among those aged 16-24y (16.6% men, 22.4% women) and decreased with age (<1.5% among those aged 45-74y). Approximately 18% of those 16-44y (n=771 men; n=1080 women) reported unsafe sex; of these, >75% had not attended a SHC in the past year. Among those reporting unsafe sex, non-attenders were older, and less likely to report >2 partners and/or concurrent partners (past year). Most of these non-attenders did not report chlamydia (73% men, 41% women aged <25; 86% men, 73% women aged 25+) or HIV (97% men, 93% women) testing elsewhere (past year). The majority reporting unsafe sex who had previously attended a SHC would seek STI care there (72% men, 66% women), whereas most who had not would go to general practice (66% men, 77% women). Conclusion: While SHC attendance was more likely among those reporting STI risk behaviour, many reporting unsafe sex had not attended and most of these did not report chlamydia or HIV tests, indicating they are not receiving sexual healthcare elsewhere. This is of more concern for those at higher STI risk for example the younger, MSM and those with concurrent partners, although higher proportions of younger people reported Chlamydia testing elsewhere. We used unsafe sex as one measure of exposure to risk, which does not take into account characteristics of partner(s) and the wider sexual network. Further improvements are necessary to reach those at-risk, including through effective, diverse service provision.